Studies on myasthenia gravis in dogs and cats - Mignan, Thomas (2023)
Myasthenia is a term used to describe impairment of neuromuscular transmission. Its etymology is derived from the Greek “myasthenia” meaning muscle weakness. Both a congenital and an acquired form exist, each with a different pathophysiology, clinical presentation, list of differential diagnoses, diagnostic approach, treatment, and outcome. Myasthenia is considered one of the most completely understood neuromuscular diseases in dogs and cats, however there are several aspects which warrant further investigations. The long-term outcome of cats with myasthenia gravis (MG) remains incompletely understood with conflicting results published to date, although it has generally been unfavourable in recent studies. Furthermore, the natural course of MG in cats has not been investigated to date. Myasthenia gravis is currently classified in dogs and cats according to generalisation, progression, and severity of skeletal muscle weakness and fatigability based on a previous classification system used for humans which has not been updated in over twenty-five years. However, factors such as the presence or absence of a thymoma, or administration of thiourylene medication in cats, can influence treatment, outcome, or both, frequently leading to the division of affected dogs and cats into separate disease groups based on these factors. Historically, congenital myasthenic syndromes (CMSs) were termed congenital MG which was thought to solely be the result of a postsynaptic deficiency of acetylcholine receptors (AChRs) in the absence of antibodies directed against them. However, it is now clear a congenital post-synaptic acetylcholine receptor (AChR) deficiency is only one of several clinically heterogeneous congenital myasthenic syndromes affecting the neuromuscular junction (NMJ), resulting in skeletal muscle weakness and fatigability. These syndromes are collectively referred to as CMSs and considered as a separate disease entity from MG. There is currently no established classification system for CMSs in dogs and cats. A significantly higher incidence of MG associated megaoesophagus (88%) is reported in dogs compared to cats (40%), or even humans in which there are only a few cases reported. This has been attributed to the tunica muscularis of the canine oesophagus being described as solely composed of skeletal muscle as opposed to that of cats or humans in which the distal third and two thirds are respectively reported to contain smooth muscle. Recently, however, the distal third of the tunica muscularis was reported to be composed of smooth muscle in a population of eight Iraqi dogs. From this, the aims of the present thesis were the following: • Evaluate the long-term outcome of cats with MG without evidence of a cranial mediastinal mass (CMM). • Evaluate the natural course of the disease in cats with myasthenia gravis without evidence of a CMM. • Update the classification system used for MG in dogs and cats based on comparison with published classification systems in human beings. • Establish a classification system for CMSs in dogs and cats. • Evaluate the tunica muscularis composition of the oesophagus in dogs.